Analysis of Law Enforcement of Dog Smuggling Crime in Kulon Progo Re-gency: Case Study on Decision Number 95/Pid.Sus/2021/PT YYK - Sawitri, Kiki Novita; Anditya, Ariesta Wibisono (IHSA Institute, 2025)
This research analyzes the law enforcement of dog smuggling in Kulon Progo Regency with a case study of Decision Number 95/Pid.Sus/2021/PT YYK. Dog smuggling not only violates the law, but also poses a public health risk, especially related to the spread of rabies. The research method used is normative-empirical juridical with the approach of legislation, case studies, and systematic literature review. The results show that there is a discrepancy in the application of criminal sanctions by judges with the special minimum provisions in Article 89 paragraph (2) of Law No. 41/2014. In addition, the DIY Agriculture and Food Security Office has a strategic role, but faces resource constraints and regulatory gaps. This research emphasizes the importance of synergy between agencies, strengthening local policies, and increasing public awareness as an effort to prevent animal smuggling. The findings are expected to be an academic contribution and input for the formulation of more effective law enforcement policies against animal smuggling crimes, especially dogs.